Assessment of bioaccumulation and detoxification of cadmium in soil-plant-insect food chain. (September 2019) - Dutta, Munmi; Kushwaha, Anamika; Kalita, Sarbeswar; Devi, Gitika; Bhuyan, Mantu
Abstract: The present study investigated the accumulation of Cd (II) and its transfer through the soil-plant ( Ricinus communis L.) - insect ( Samia ricini Donovan) terrestrial food web and detoxification mechanisms involved. Cd accumulation in R. communis L. followed the order: roots ˃ stems ˃ leaves. With the increase in Cd concentration in plant, increase in Cd accumulation in larvae was observed. Transfer of Cd (II) was highest from soil to root followed by larvae to excreta, root to leaf and leaf to larvae. Sub-cellular partitioning of Cd was performed in the larval bodies to determine possible detoxification strategies by the insect larvae. Heat stable protein was found to be the dominant metal-binding compartment of Cd. The results revealed a dose dependent increase in Cd (II) concentration along food chain. The excretion pattern of Cd by the silkworm larvae and sub-cellular distribution showed sequestration of Cd feeding on Cd treated R. communis leaves. Highlights: Cd accumulation in Ricinus communis followed the order: roots ˃ stems ˃ leaves. Cd accumulation in larvae increased with increasing metal concentration in plant. Cd is principally bound to heat stable protein in larvae. Subcellular study reveals the detoxification and transfer of Cd in food web.